Recurrent Cesarean Scar Ectopic Pregnancy Treated with Systemic Methotrexate - Chima Ndubizu; Rodney A. McLaren; Sandra McCalla; Mohamad Irani (Case Reports in Obstetrics and Gynecology)
Cesarean scar pregnancy (CSP) is a rare event; however its incidence has been rising due to the increasing rates of cesarean deliveries. The majority of cases present with signs or symptoms requiring surgery, which often results in hysterectomy. The recurrence of CSP is even rarer with only few cases which have been reported. This is a report of recurrent cesarean scar ectopic pregnancy (RCSP) that was promptly diagnosed and managed with only systemic methotrexate. This was a 30-year-old woman, with a history of two prior cesarean deliveries followed by a CSP, who presented at 5 weeks and 3 days of gestation for her first prenatal visit. Transvaginal ultrasound revealed a RCSP. Her serum beta-human chorionic gonadotropin (β-hCG) level was 54,295 IU/L. The first CSP, which was diagnosed at a later stage, was treated with uterine artery embolization and systemic methotrexate leading to complete resolution within 10 weeks. The current ectopic was treated with two doses of systemic methotrexate; her serum β-hCG reached undetectable levels within 7 weeks. Thus, patients with a history of prior CSP should be carefully monitored with transvaginal ultrasound during subsequent pregnancies to allow early diagnosis of RCSP, which could then be treated conservatively.